OSSEOUS METAPLASIA OF ENDOMETRIUM -A RARE CAUSE OF MENOMETRORRHAGIA - Fawad, Saadia (Journal of Ayub Medical College Abbottabad, 2012)
Osseous metaplasia is a rare disorder of endometrium in which a bone is formed from a different tissue inside the same individual. It is not generally applicable to the persistence of embryonic or foetal bone resulting in calcification or ossification. Most common presentation of osseous metaplasia of bone is infertility usually secondary. A case of osseous metaplasia as a cause of memetrorrhagia as a rare entity is presented.